2020
DOI: 10.34087/cbusbed.719686
|View full text |Cite
|
Sign up to set email alerts
|

Son Sınıf İlk ve Acil Yardım Programı Öğrencilerinin Eğitim Düzeyi ve Yeterlilik Algı Durumlarının Belirlenmesi

Abstract: Son sınıf ilk ve acil yardım programı öğrencilerinin mesleki uygulama yapma sayıları, pratik yeterlilikleri ve teorik bilgi düzeylerinin değerlendirilmesi amaçlandı. Gereç ve Yöntemler: Tanımlayıcı tipte yapılan bu araştırma bir devlet üniversitesi İlk ve Acil Yardım Programı 2. sınıfta aktif öğrenim gören 96 öğrenci ile yapıldı. Katılımcıların mesleki konularda eğitim alıp almadıkları (17 soru), uygulama yapıp yapmadıkları (11 soru), kendilerini yeterli görüp görmedikleri (16 soru) ve bilgi düzeylerini belirl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…In this research, the increase in students' perceptions of proficiency after training is an important finding that shows the positive effect of simulation training. Similar to this research, Sandy et al in their study in South Africa and Negri et al in their study evaluating 53 separate articles found that simulation training had a positive effect on the perception of students' professional self-efficacy (Negri et al, 2017;Sandy, Meyer, Oduniyi & Mavhandu-Mudzusi, 2021;Tosun, 2009;Yaşar Can & Dilmen Bayar, 2020).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In this research, the increase in students' perceptions of proficiency after training is an important finding that shows the positive effect of simulation training. Similar to this research, Sandy et al in their study in South Africa and Negri et al in their study evaluating 53 separate articles found that simulation training had a positive effect on the perception of students' professional self-efficacy (Negri et al, 2017;Sandy, Meyer, Oduniyi & Mavhandu-Mudzusi, 2021;Tosun, 2009;Yaşar Can & Dilmen Bayar, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…In the evaluation of the number of applied vocational practices, besides the rate of "none" was higher, also application numbers were lower when compared to previous studies (Table 2) (Gürbüz et al, 2019;Tosun, 2009;Yaşar Can & Dilmen Bayar, 2020;Yıldırım, ISSN: 2147-7892, Cilt 10 Sayı 2 (2022) 438-449 doi: 10.33715/inonusaglik.1052579 Investigation of the Effect of Simulator Usage on Advanced Life Support and Labor Help Qualifications, and Self-Efficacy of Paramedic Students Perihan GÜRBÜZ, Serdar DERYA, Gülsüm YETİŞ KOCA, Turgay KOLAÇ, Zehra Deniz ÇIRAK 445 2017). The two main reasons for this situation may be the application inadequacies brought by the pandemic process and the lower number of vocational high school graduates in the relevant field compared to previous studies.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations